Public perceptions of barriers to walk in urban areas of Lahore, Pakistan - Ahsan, Muhammad; Shakeel, Nabeel; Baig, Farrukh (UNIV STUDI NAPOLI FEDERICO II, DIPT PIANIFICAZIONE & SCIENZA TERRITORIO, 2023)
The development strategies in urban areas of the less developed world have predominantly focused on motorized-oriented planning, which influences the travel habits of individuals. However, there has been little research on walking as a mode of transport in Pakistani cities. In order to bridge this gap, this study examines the public's perception of barriers to walking in Lahore, Pakistan. Surveys were conducted online using structured questionnaires. To investigate pedestrians' perceptions of walking constraints, a valid sample of 277 responses was analyzed using a weighted factor and regression analysis. Findings show that pedestrians' dissatisfaction with existing infrastructure is due to the ignorance of walking as a travel mode in transport plans, policies, and strategies executed by government organizations. The integration of walking as a travel mode has been highly neglected by transport policymakers. Further, significant walking constraints have been elaborated that need to be resolved to enhance walking in urban areas.
Keywords: Walking; Pedestrian perceptions; Accessibility; Walking constraints; Lahore; WALKABILITY; ENVIRONMENT; DESIGN; SPACE; GREEN; Urban Studies